1997
DOI: 10.1021/ic970355s
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic Neutron Scattering, Infrared, and Raman Spectroscopic Studies of Mg2FeH6 and Mg2FeD6

Abstract: The combination of the three types of vibrational spectroscopy, infrared, Raman, and inelastic neutron scattering, has enabled all of the internal, and most of the external, modes of Mg2FeH6 and Mg2FeD6 to be observed and assigned, as well as some of the modes of Mg2FeD5H. As an aid to the assignment, a reliable, empirical force field has been developed. The spectra also show evidence for a dynamic distortion of the hexahydrido complex, an effect that is not observed for the deuterated species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 10 publications
5
40
1
Order By: Relevance
“…Table I also gives the full symmetry A g Raman phonon frequency associated with the H internal structural parameter. Raman and inelastic neutron scattering measurements 14 for Mg 2 FeH 6 yield an experimental frequency of 1873 cm −1 , in good agreement with the present LDA value of 1923 cm −1 . The LDA frequencies follow the reported trend for H bond stretching modes in infrared data, 5 decreasing with increasing D ionic radius, and increasing with increasing M atomic number.…”
Section: Electronic Structure and The Eighteen Electron Rulesupporting
confidence: 89%
“…Table I also gives the full symmetry A g Raman phonon frequency associated with the H internal structural parameter. Raman and inelastic neutron scattering measurements 14 for Mg 2 FeH 6 yield an experimental frequency of 1873 cm −1 , in good agreement with the present LDA value of 1923 cm −1 . The LDA frequencies follow the reported trend for H bond stretching modes in infrared data, 5 decreasing with increasing D ionic radius, and increasing with increasing M atomic number.…”
Section: Electronic Structure and The Eighteen Electron Rulesupporting
confidence: 89%
“…n n 5 lengths any further explanation remains too speculative. for purposes of comparison [2]. Eu RuH are much weaker than those of the other samples 2 6 It has been reported that Raman intensities for XY which are gray.…”
Section: Resultsmentioning
confidence: 98%
“…The IR pattern correlated well with the data reported for pure LiBH 4 [29], demonstrating that LiBH 4 was present in the rehydrogenated material. The asymmetric stretching vibration of [FeH 6 ] 4− at 1785 cm −1 was also seen [30]. The PCT plots of the dehydrogenation part during the reversible hydrogenation tests at 673 K are shown in Figure 7.…”
Section: Reversible Hydrogenation Due To the Optimal Composition Ratiomentioning
confidence: 79%